AB0152 Disease activity and damage scores correlated differently with the patient reported outcomes in patients with primary SJÖGREN'S syndrome compared to lupus associated with secondary SJÖGREN'S syndrome. (15th June 2017) - Thompson, N; Gupta, V; Gandhi, A; Radmore, R; Cho, S; Isenberg, DA; Jury, EC; Ciurtin, C
Abstract : Background: Previous studies showed a poor correlation between EULAR Sjögren's Syndrome Patient Reported Index (ESSPRI) and EULAR Sjögren's Syndrome Disease Activity Index (ESSDAI) in patients with Sjögren's syndrome (SS) (1). There are no previous studies correlating these scores with the SS Disease Damage Index (SSDDI) or assessing comparatively patients with primary (pSS) and secondary SS associated with lupus (SLE/SS). Objectives: We aimed to assess how well scores assessing disease activity, damage and patient reported outcomes correlate with each other in patients with pSS compared to SLE/SS. Methods: We conducted a cross-sectional study of 55 patients with pSS and 15 SLE/SS. Detailed clinical and laboratory data, along with patient reported outcomes (ESSPRI) and disease activity and damage scores (ESSDAI, BILAG and SSDDI) were collected. We compared the clinical and laboratory parameters of the two patient groups (pSS and SLE/SS) and assessed the correlations between maximum ESSDAI score since diagnosis and ESSDAI, ESSPRI, SSDDI and BILAG scores at the time of assessment. Results: The table below shows comparatively the differences between the pSS and SLE/SS patient groups. We found significant correlations of SSDDI score with disease duration and maximum ESSDAI score in patients with pSS (r=0.27, p=0.05 and r=0.67, p=0.0001, respectively). In SLE/SS patients, ESSPRI scores correlated with both BILAG and maximum ESSDAI score (r=0.55, p=0.03 and r=0.7, p=0.02, respectively). The SSDDI score correlated with the disease duration only in pSS patients (r=0.27, p=0.05). Conclusions: Our study showed that there was no similar correlation between various disease scores in patients with pSS compared to SLE/SS patients. If the patient reported outcomes correlated with the disease activity (ESSDAI and BILAG) in SLE/SS patients, this correlation was not seen in pSS patients, in which the significant correlations were found only between damage scores, highest disease activity score and disease duration. References: Responsiveness of disease activity indices ESSPRI and ESSDAI in patients with primary Sjögren's syndrome treated with rituximab, Ann Rheum Dis 2012;71:. Disclosure of Interest: None declared